Primary Angiosarcoma of the Pericardium. Case Report and Review of the Literature - Timóteo, AT (2010)
Primary cardiac tumours are rare entities and angiosarcoma is the most frequent primary cardiac malignant tumour. Mean survival is six months and the tumour responds poorly to chemotherapy. We present the case of a 50 year-old patient with localised pericardial angiosarcoma who survived 23 months after diagnosis with a combined approach of chemotherapy and surgery.